La búsqueda de la armonía en la diversidad : el diálogo ecuménico e interreligioso desde el Concilio Vaticano II - Pérez Prieto, Victorino (Editorial Verbo Divino, 2014)
Interreligious dialogue is increasingly necessary in a world of religious and cultural pluralism. This dialogue is not new; however, as indicated in the Prologue by J. Melloni, is still a virgin territory to explore, which is necessary to combine fidelity to one's own tradition and at the same time, oen to the mystery of God, the human being and the world from what is experienced in other traditions. This joint is difficult which this book aims.